Toner for electrostatic charge image development and production method for toner for electrostatic charge image development
Patent Information
- Application Number
- JP2023128747
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2043-08-07
AI Technical Summary
【0035】 これにより、ポリメチルシルセスキオキサンの帯電受容性に対する影響が比較的小さいサリチル酸金属塩を適宜添加することにより、印刷機に応じた帯電性の調整が容易となる。 したがって、高画質な印字が可能となり、帯電速度および印刷速度を速くし、機内汚染等の防止もすることができる。
Smart Images

Figure 2025024556000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner for developing electrostatic images and a method for producing the toner for developing electrostatic images, for example, to a toner for developing electrostatic images used in an electrophotographic image forming method and a method for producing the toner for developing electrostatic images. [Background technology]
[0002] In recent years, there has been an increasing demand for electrophotographic image forming apparatuses with higher device speeds, higher definition, more stable image quality, etc. In order to meet such demands, electrophotographic developers are required to have high performance magnetic carriers with excellent charging properties, etc.
[0003] For example, Patent Document 1 (JP Patent Publication 63-101854 A) proposes an electrostatic image developer that has excellent workability during toner production, that hardly causes aggregation between toner powder particles, and that can significantly suppress the occurrence of contamination of carriers and photoconductor surfaces, and that is made of a toner that exhibits strong negative charging characteristics.
[0004] The electrostatic image developer described in Patent Document 1 is characterized by being made of a toner having negative charging properties and containing independent, nearly spherical, polymethylsilsesquioxane powder.
[0005] Patent Document 2 (WO 2015 / 107961) proposes hydrophobic, small-particle-sized polyalkylsilsesquioxane microparticles, an external toner additive and a dry toner for electrophotography using the same, and a method for producing hydrophobized spherical polyalkylsilsesquioxane microparticles.
[0006] The external toner additive described in Patent Document 2 is characterized in that it is hydrophobized spherical polymethylsilsesquioxane fine particles having a mass-based median diameter measured by centrifugal sedimentation method within the range of 0.05 to 0.3 μm.
[0007] Patent Document 3 (JP Patent Publication No. 9-197705) proposes an efficient method for producing organic-inorganic composite particles that are excellent in various properties such as hardness, mechanical strength, elasticity, hydrophobicity, etc. and are suitable as toner additives, etc.
[0008] The method for producing organic-inorganic composite particles described in Patent Document 3 includes a hydrolysis step in which at least one hydrolyzable / condensable silicon compound selected from compounds represented by a specific general formula is hydrolyzed in the presence of an acid to obtain a hydrolysate and / or a condensate thereof, and a polycondensation step in which the hydrolysate and / or the condensate thereof is polycondensed in the presence of a base, and a polymer having a group represented by another general formula is present in either or both of the hydrolysis step and the polycondensation step.
[0009] Patent Document 4 (JP Patent Publication No. 9-194593) proposes organic-inorganic composite particles which are excellent in various properties such as hardness, mechanical strength, elasticity, and hydrophobicity, and are suitable as a toner additive.
[0010] The organic-inorganic composite particles described in Patent Document 4 are obtained by subjecting a silicon compound (A) represented by a specific general formula to a cohydrolysis-polycondensation reaction with a silicon compound (B) represented by another general formula. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Unexamined Patent Publication No. 63-101854 [Patent Document 2] International Publication No. 2015 / 107961 [Patent Document 3] Japanese Patent Application Publication No. 9-197705 [Patent Document 4] Japanese Patent Application Publication No. 9-194593 Summary of the Invention [Problem to be solved by the invention]
[0012] In the two-component development method, in an image forming method using electrostatic printing or the like, charged toner particles are configured to develop an electrostatic latent image on a photosensitive drum by electrostatic force corresponding to the potential difference on the drum. In this case, the toner is charged by friction between toner particles or between the toner and the carrier, and further with a regulating blade, etc. For this reason, it is essential to control the particle size and chargeability of the toner.
[0013] Conventionally, negatively charged charge control agents include metal complex salts of monoazo dyes, nitrohumic acid and its salts, zinc salicylate, aluminum salicylate, alkylsalicylic acid, dialkylsalicylic acid, naphthoic acid, dicarboxylic acid, and other metal compounds, boron compounds, urea compounds, silicon compounds, calixarene, sulfonated copper phthalocyanine pigments, chlorinated paraffin, dimethylpolysiloxane, dry silica, and acrylic organic fine particles. However, these charge control agents have complex structures and poor stability. In addition, they are easily decomposed or altered by decomposition during thermal kneading, mechanical impact, friction, changes in temperature and humidity conditions, and the like, and may reduce charge controllability.
[0014] To solve such problems, Patent Document 1 uses polymethylsilsesquioxane as an internal additive, which is a charge control agent, and Patent Documents 2 to 4 use organic-inorganic composite particles as an external additive.
[0015] Conventionally, it was believed that the charge control agent of a two-component toner must be present to some extent on the toner surface in order to impart triboelectric charging ability. Therefore, as in Patent Document 1, it is believed that the larger the particle size of the charge control agent, the higher the probability that it will be present on the outermost surface of the toner. However, it was found that as the particle size becomes larger, the charge control agent becomes localized in the toner, resulting in uneven charging, sudden toner scattering and fogging, which causes problems such as changes in image density and deterioration of image quality. In addition, in Patent Documents 2 to 4, polymethylsilsesquioxane powder is used as an external additive, but since it has low mechanical strength, it is easily crushed during mixing in subsequent processes, and there is a problem that it cannot fully function as a charge control agent.
[0016] The present inventors discovered that by adding polymethylsilsesquioxane particles having a predetermined particle size to a toner, the toner can function as a charge control agent for a negatively charged toner, resulting in significantly excellent charging properties, and thus arrived at the present invention. An object of the present invention is to provide an electrostatic image developer capable of producing high quality prints and a method for producing the electrostatic image developer. Another object of the present invention is to provide an electrostatic image developer excellent in chargeability and thixotropy, and a method for producing the electrostatic image developer. Another object of the present invention is to provide an electrostatic image developer which has a large saturated charge amount, a fast charging speed and excellent environmental stability, and a method for producing the electrostatic image developer. [Means for solving the problem]
[0017] (1) According to one aspect, the toner for developing electrostatic images contains a binder resin, a colorant, a release agent, and a charge control agent, the charge control agent being composed of polymethylsilsesquioxane particles and being added to the toner for developing electrostatic images, the polymethylsilsesquioxane particles having an average particle diameter of 0.05 μm or more and 0.3 μm or less, and an absolute value of the saturated charge amount being 30 μC / g or more.
[0018] In the toner for developing electrostatic images of the present invention, by adding polymethylsilsesquioxane particles having an average particle diameter of 0.05 μm or more and 0.3 μm or less as a charge control agent, it is possible to obtain a toner with a large saturated charge amount, improved charging speed, and excellent uniform charging ability. That is, according to conventional common knowledge, in order to realize a uniformly charged toner, it is preferable to have a charge control agent present on the toner particle surface as much as possible to ensure sufficient friction with the carrier, and to increase the surface coverage. However, when large-sized polymethylsilsesquioxane particles are present, the polymethylsilsesquioxane particles are crushed during the kneading process, etc., and it becomes difficult for them to be present uniformly on the toner surface. This causes fogging, cleaning failure, etc. On the other hand, by using the polymethylsilsesquioxane particles having an average particle diameter of 0.05 μm or more and 0.3 μm or less used in the present invention as an internal additive, they are uniformly mixed with the binder resin, release agent, etc., and can be uniformly present throughout the entire toner particle (inside and surface), thereby preventing printing defects such as fogging and cleaning defects.
[0019] In particular, the inventors have discovered that by adding polymethylsilsesquioxane particles having a predetermined particle size to the inside of the toner, the toner has a large saturated charge amount and a high charging speed. This is believed to be because the polymethylsilsesquioxane dispersed inside the toner improves charge acceptance, increasing the saturated charge amount of the entire toner, accelerating the charging speed, and further contributing to charge retention (reducing the amount of leakage). In other words, friction with the carrier generates charges at the charge generation sites present on the toner surface, and the polymethylsilsesquioxane inside the toner functions as a charge acceptance site to retain the charge, making it possible to accept a large amount of charge at high speed and also making it difficult for the charge to leak into external water vapor, etc. It is believed that the siloxane skeleton and methyl groups are involved in this, but the details are unknown. According to the present invention, a sufficient amount of charge can be obtained immediately, and therefore a toner with a uniform and high amount of charge can be obtained, which enables high-quality printing, prevents contamination inside the machine, and increases the printing speed.
[0020] Furthermore, the inventors discovered that the thixotropy of the toner is improved by adding polymethylsilsesquioxane particles of a specific particle size to the inside of the toner. In other words, when external stress is applied, the viscosity η' of the entire toner drops significantly, and when the stress is removed, the viscosity returns to the original value. This is thought to be related to the network structure of siloxane, but the details are unknown. According to the present invention, the thixotropy of the toner is improved, so that the viscosity of the toner is reduced by the pressure of the fixing roller, and the toner can be fixed favorably to the printing paper. The saturated charge amount of the present invention can be measured by charging the toner (1 part by mass) and the ferrite carrier (9 parts by mass) in a ball mill (120 rpm) and using a suction type charge amount measuring device, as described in detail in the charge amount measurement of the embodiment.
[0021] (2) The electrostatic image developing toner according to a second aspect of the present invention is the electrostatic image developing toner according to one aspect of the present invention, wherein the charge control agent comprises polymethylsilsesquioxane particles and an aluminum salt of a salicylic acid derivative.
[0022] The toner for developing electrostatic images according to the second invention contains only polymethylsilsesquioxane particles and an aluminum salt of a salicylic acid derivative as the charge control agent, and therefore can be a toner having improved chargeability and thixotropy. In particular, when another charge control agent (CCA) is added to polymethylsilsesquioxane, the chargeability tends to deteriorate, and it is considered that the charge acceptance of polymethylsilsesquioxane is inhibited. However, the inventors have discovered that, among the charge control agents, the aluminum salt of a salicylic acid derivative has a relatively small effect on the charge acceptance of polymethylsilsesquioxane. Therefore, by adding an appropriate amount of an aluminum salt of a salicylic acid derivative as a charge control agent, it becomes easy to adjust the chargeability according to the printing machine.
[0023] That is, unlike other charge control agents, the aluminum salt of a salicylic acid derivative is unlikely to inhibit the function of polymethylsilsesquioxane as a charge receiving site, and can be used as an agent for adjusting the chargeability of a toner.
[0024] (3) The electrostatic image developing toner according to a third aspect of the present invention may be such that, in the electrostatic image developing toner according to one aspect of the present invention, the absolute value of the charging speed is 6.0 μC / g·min or more.
[0025] This makes it possible to minimize uneven charging, enabling high speed, high quality printing.
[0026] (4) The electrostatic image developing toner according to a fourth aspect of the present invention is the electrostatic image developing toner according to any one of the first to third aspects of the present invention, wherein the binder resin includes a polyester resin.
[0027] This is preferable because it ensures storage stability, high-temperature offset resistance, charge stability and durability, and enables printing of higher image quality.
[0028] (5) The electrostatic image developing toner according to the fifth invention may contain 1 part by weight or more and 8 parts by weight or less of polymethylsilsesquioxane particles per 100 parts by weight of the binder resin in the toner according to any one of the first to fourth aspects.
[0029] When the blending ratio of the binder resin, the release agent and the polymethylsilsesquioxane particles is within the above range, the polymethylsilsesquioxane particles can be present at a suitable concentration in the toner for developing electrostatic images. In particular, by having the content of the polymethylsilsesquioxane particles within the above range, the particles are suitably added to the toner, and the proportion of polymethylsilsesquioxane exposed on the toner surface becomes suitable, so that stable charging performance can be achieved. Therefore, charge leakage can be preferably prevented, and the amount of charge on the toner can be made more uniform.
[0030] (6) The toner for developing electrostatic images according to the sixth invention may be the toner for developing electrostatic images according to any one of the first to fifth inventions, wherein the ratio of average particle diameters of the toner for developing electrostatic images and the polymethylsilsesquioxane particles (toner particles / polymethylsilsesquioxane particles) is 25 or more and 150 or less.
[0031] When the ratio of the average particle size of the electrostatic image developing toner to the average particle size of the polymethylsilsesquioxane particles is within the above range, the polymethylsilsesquioxane particles are preferably added to the interior of the toner particles, and the proportion of polymethylsilsesquioxane exposed on the toner surface becomes favorable. Therefore, a toner having improved chargeability and thixotropy can be obtained.
[0032] (7) According to another aspect, a method for producing a toner for developing electrostatic images includes a kneading step of kneading a binder resin, a colorant, a charge control agent, and a release agent to obtain a kneaded mixture, a pulverization step of pulverizing the kneaded mixture to obtain a mother toner having an average particle size of 5 μm or more and 10 μm or less, and an external addition step of adding amorphous silica and / or titanium oxide to the mother toner, wherein the charge control agent internally added to the kneaded mixture is composed of polymethylsilsesquioxane particles having an average particle size of 0.05 μm or more and 0.3 μm or less.
[0033] As a result, the polymethylsilsesquioxane particles are preferably incorporated as a charge control agent in the toner for developing electrostatic images, and therefore excellent charging performance and thixotropy can be exhibited. Therefore, high quality printing is possible, charging speed and printing speed are increased, and contamination inside the machine can be prevented.
[0034] (8) The eighth aspect of the present invention relates to a method for producing a toner for developing electrostatic images, wherein in the method for producing a toner for developing electrostatic images according to the seventh aspect of the present invention, the charge control agent added to the kneaded product may comprise polymethylsilsesquioxane particles having an average particle diameter of 0.05 μm or more and 0.3 μm or less and a metal salicylate.
[0035] This makes it easy to adjust the chargeability according to the printing machine by appropriately adding a metal salicylate, which has a relatively small effect on the charge receptivity of polymethylsilsesquioxane. Therefore, high quality printing is possible, charging speed and printing speed can be increased, and contamination inside the machine can be prevented. [Brief description of the drawings]
[0036] [Figure 1] FIG. 13 is a graph showing the friction time dependence of toner charge amount (comparison between types of charge control agent and the presence or absence of charge control agent). [Diagram 2] FIG. 13 is a graph showing the friction time dependence of the toner charge amount (comparison between different types of charge control agents). [Diagram 3] FIG. 1 is a graph showing the friction time dependence of toner charge amount (comparison based on the amount of polymethylsilsesquioxane particles added). [Figure 4] FIG. 1 is a graph showing the temperature dependence of storage modulus (comparison based on the amount of polymethylsilsesquioxane particles added). [Diagram 5] FIG. 1 is a graph showing the temperature dependence of storage modulus (comparison between different types of charge control agents). [Figure 6] FIG. 1 is a graph showing the shear rate dependency of dynamic viscosity (comparison based on the amount of polymethylsilsesquioxane particles added). [Figure 7] FIG. 1 is a graph showing the shear rate dependence of dynamic viscosity (comparison between types of charge control agents). [Figure 8] FIG. 2 is a SEM diagram showing an example of the arrangement of polymethylsilsesquioxane particles in a cross section of the toner according to Example 1 of the present invention. [Figure 9] FIG. 11 is a SEM diagram showing an example of the arrangement of polymethylsilsesquioxane particles in a cross section of a toner according to Example 4 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] [Present embodiment] The toner for developing electrostatic images according to the present embodiment contains a binder resin, a colorant, a release agent, and polymethylsilsesquioxane particles in a mixed state. That is, a charge control agent is generally added to a toner in order to stably impart an electrostatic charge, and it is believed that the charge control agent present on the surface of the toner rubs against the carrier or the like to impart an electrostatic charge. On the other hand, the toner for developing electrostatic images of the present embodiment has polymethylsilsesquioxane particles added to the inside of the toner, thereby improving the charge acceptance of the toner and enabling high-quality printing. The toner of the present embodiment is particularly suitable as a negatively charged toner. The toner for developing electrostatic images according to the present embodiment will be described in detail below.
[0038] (Binding resin) The binder resin is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include polyester resin, styrene-acrylic resin, polyol resin, vinyl resin, polyurethane resin, epoxy resin, polyamide resin, polyimide resin, silicon resin, phenol resin, melamine resin, urea resin, aniline resin, ionomer resin, polycarbonate resin, etc. These may be used alone or in combination of two or more. Among these, styrene-acrylic resin or polyester resin is preferred because it can impart flexibility to the toner and has a relatively high glass transition point.
[0039] In the resin composition of the present embodiment, the glass transition point of the styrene-acrylic resin or polyester resin is preferably 45° C. or more and 70° C. or less, more preferably 45° C. or more and 55° C. or less, and most preferably 48° C. or more and 52° C. or less. This allows the toner to be reliably fixed to paper even at low temperature fixing, and also makes it possible to obtain a toner with excellent offset resistance. Among the styrene-acrylic resin and the polyester resin, the polyester resin is more preferable from the viewpoint of electrostatic chargeability.
[0040] (Polyester resin) The polyester resin in the present embodiment may be a polyester resin, a polyester urethane resin, or a mixture thereof. When a resin composition containing a polyester resin is used, a toner having a relatively high viscosity is formed, and therefore the high temperature offset property is improved.
[0041] The polyester resin may be a blend of a high molecular weight component and a low molecular weight component, and a polyester resin having a wide molecular weight distribution is more preferable. In addition, examples of polyester resins include linear polyester resins and nonlinear polyester resins, and nonlinear polyester resins are preferred from the viewpoints of storage stability, high-temperature offset resistance, electrostatic stability, and durability. The polyester resin may be a resin having a structure in which polyester is crosslinked by a carbon-carbon bond. The polyester referred to here is not particularly limited, and may be any polyester that can be crosslinked by a carbon-carbon bond. Among them, polyesters having a carbon-carbon double bond are preferred from the viewpoint of easiness in forming a crosslinked structure. The number average molecular weight of the polyester resin is preferably from 2000 to 6000, more preferably from 3000 to 5000. The most preferable number average molecular weight of the polyester resin is about 4000. The weight average molecular weight of the polyester resin is preferably 8,000 or more and 40,000 or less, more preferably 10,000 or more and 30,000 or less, and most preferably 12,000 or more and 20,000 or less.
[0042] The number average molecular weight and weight average molecular weight of the polyester resin can be measured by gel permeation chromatography (GPC). For example, the molecular weight can be calculated as polymethyl methacrylate using a solvent such as tetrahydrofuran or water as an eluent.
[0043] The polyester resin in the present embodiment may be surface-modified. For the purpose of adjusting the chargeability of the toner, improving particle dispersibility, improving heat resistance, etc., it is preferable to surface-modify the binder resin. For the surface modification of the polyester resin, a carbodiimide compound, silicone oil, silane coupling agent, etc. can be used.
[0044] (Release agent) The toner for developing electrostatic images in this embodiment contains a release agent, which melts instantly during thermal fixing and seeps out of the toner to form an oil film on the heating roller, preventing offset of the toner and increasing gloss. The release agent is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include low molecular weight polyolefins such as polyethylene, ester waxes such as stearyl stearate, vegetable waxes such as carnauba wax, rice wax, candelilla wax, wood wax, jojoba oil, animal waxes such as beeswax, mineral and petroleum waxes such as montan wax, ozokerite, ceresin, paraffin wax, microcrystalline wax, Fischer-Tropsch wax, ester wax, and modified products thereof. These waxes can be used alone or in combination. In particular, aliphatic hydrocarbons such as paraffin wax, ester wax, and Fischer-Tropsch wax are preferably used. The Fischer-Tropsch wax may be modified Fischer-Tropsch wax. A higher fatty acid may also be used. For example, oleic acid, myristic acid, linoleic acid, linolenic acid, stearic acid, lauric acid, capric acid, 12-hydroxystearic acid, and behenic acid may be used. Of these, 12-hydroxystearic acid is preferred.
[0045] In the present embodiment, an example is shown in which paraffin wax is used as the release agent. In the pulverization process, the wax is preferably hard, since it is intended to have good pulverizability and prevent the wax from being exposed to the toner surface. Although low-melting paraffin wax is relatively soft and may be considered unsuitable for the pulverization process, it is possible to increase the hardness by narrowing the molecular weight distribution, and it can be applied to pulverized toner. In addition, by narrowing the carbon number distribution, it has excellent performance in suppressing bleeding of the release agent during kneading and pulverization in pulverized toner, reducing ultrafine particles during printing, preventing blocking between toners, and low-temperature fixation or high-speed printing due to good thermal response. Furthermore, since it is rich in saturated linear hydrocarbons as described above, it is difficult to dissolve in polyester resin, and a small amount of the compounding can provide a release effect.
[0046] The melting point of the release agent is preferably 60° C. or higher and 120° C. or lower, more preferably 70° C. or higher and 90° C. or lower, from the viewpoints of low-temperature fixability, releasability and glossiness of the toner in the electrophotographic system.
[0047] The content of the release agent is preferably 1 part by weight or more and 13 parts by weight or less, more preferably 1.2 parts by weight or more and 10 parts by weight or less, and even more preferably 1.5 parts by weight or more and 8 parts by weight or less, relative to 100 parts by weight of the binder resin.
[0048] (Polymethylsilsesquioxane) In the present invention, polymethylsilsesquioxane particles are added to and mixed with a binder resin, a release agent, and a colorant, so that the polymethylsilsesquioxane particles function as a charge control agent in the toner. This makes it possible to realize the functions of a charge control agent, such as toner charge amount adjustment, improved charge rise property, improved environmental stability, uniform charge amount distribution, and improved long-term charge stability. The charge rise property of a toner is an index of whether or not the toner can be charged to a predetermined charge level in a short period of time.
[0049] Polymethylsilsesquioxane has a siloxane skeleton (Si-O-Si) crosslinked in a three-dimensional network, and is represented by X-SiO 1.5 The basic structure is as follows. In addition, the methyl groups present on the particle surface are hydrophobic, providing excellent electrostatic chargeability. Conventionally, silica-based dimethylpolysiloxane, silsesquioxane (SQ), etc. have been commonly used as charge control agents for toners, and they are usually precipitated on the surface of the toner to increase friction and improve the amount of charge. The toner of this embodiment contains polymethylsilsesquioxane particles (PMSSQ) with a particle size of 0.05 μm or more and 0.3 μm or less as an internal additive, which allows the particles to be uniformly present inside the toner particles, resulting in a toner with excellent chargeability. In addition, the polymethylsilsesquioxane particles used in this embodiment are preferably subjected to a hydrophobic treatment on the particle surface, which allows the toner to have a larger saturated charge amount and a faster charging speed.
[0050] By adding polymethylsilsesquioxane particles to the toner, the particles are less likely to separate from the toner particle surface, and damage to the photoreceptor or image quality defects caused by the separation can be prevented. The content of the polymethylsilsesquioxane particles is preferably 0.1 parts by weight or more and less than 10 parts by weight, more preferably 0.5 parts by weight or more and 8 parts by weight or less, and even more preferably 1.0 parts by weight or more and 5.0 parts by weight or less, relative to 100 parts by weight of the binder resin. This allows the ink to maintain a uniform and stable chargeability, makes it easy to control the chargeability, and enables printing with a constant image density and high image quality. When the content of polymethylsilsesquioxane particles in a toner increases, the thixotropy increases, but the dynamic viscoelasticity G' also tends to increase. Therefore, when the content of polymethylsilsesquioxane particles exceeds the upper limit, the increase in viscoelasticity G' has a greater effect than the improvement in thixotropy, and fixing performance may be impaired.
[0051] The polymethylsilsesquioxane particles used in this embodiment can be produced, for example, by the method described in Patent Document 2 (WO 2015 / 107961), and specifically, can be obtained by the following steps 1 to 4. Step 1: 54.0 g of water and 0.01 g of acetic acid as a catalyst were placed in a 200 ml recovery flask and stirred at 30° C. 68.0 g of methyltrimethoxysilane was added thereto and stirred for 1 hour to obtain 122.0 g of a raw material solution. Step 2: 2.8 g of 25% ammonia water, 128.0 g of water, and 383.0 g of methanol were added to a 1000 ml eggplant flask and stirred at 30° C. to prepare an alkaline aqueous medium. 122.0 g of the raw material solution obtained in step 1 was added dropwise to this alkaline aqueous medium over 1 minute. The mixture after the dropwise addition of the raw material solution was stirred for 25 minutes to allow the polycondensation reaction of the fine particle precursor to proceed, and 635.8 g of a polycondensation reaction liquid was obtained. Step 3: 2500 g of water was placed in a 5000 ml recovery flask, and 635.8 g of the polycondensation reaction liquid obtained in step 2 was added dropwise over 1 minute while stirring at 25° C. The polycondensation reaction liquid became cloudy as soon as it was mixed with the water, and 3136 g of a dispersion containing spherical polymethylsilsesquioxane microparticles was obtained. Step 4: 30.3 g of hexamethyldisilazane was added as a hydrophobizing agent to the spherical polymethylsilsesquioxane microparticle dispersion liquid obtained in step 3, and the mixture was stirred at 25°C for 48 hours to obtain a powder suspension in which the hydrophobized spherical polymethylsilsesquioxane microparticle powder was suspended in the upper layer of the liquid. After leaving the mixture to stand for 5 minutes, the floating powder was collected by suction filtration and dried under reduced pressure at 100°C for 24 hours to obtain 31.4 g of white hydrophobized spherical polymethylsilsesquioxane microparticle dry powder.
[0052] Among the above steps, step 4 is a hydrophobization treatment, and the polymethylsilsesquioxane particles of this embodiment can be preferably manufactured to have a mass-based particle size (median diameter) of 0.05 to 0.30 μm by centrifugal sedimentation method by hydrophobizing the surface with a hydrophobizing agent. Furthermore, by being hydrophobized, it is less susceptible to humidity, which is advantageous in terms of environmental stability. Furthermore, ensuring environmental stability also contributes to ensuring the charging stability of the toner. The degree of hydrophobicity of the hydrophobized polymethylsilsesquioxane particles of this embodiment is preferably 55 to 75% by volume (methanol titration method), which makes it possible to obtain a toner with low hygroscopicity and excellent charging stability while preventing particle aggregation. The polymethylsilsesquioxane particles of the present embodiment may have a particle size (median diameter) of 0.05 μm or more and 0.30 μm or less, preferably 0.08 μm or more and 0.25 μm or less, more preferably 0.08 μm or more and 0.20 μm or less. This allows the particles to be preferably added to the inside of the toner, and allows the particles to exhibit excellent charging performance. In addition, if the median diameter exceeds 0.30 μm, the added polymethylsilsesquioxane particles are easily detached from the toner particle surface, and the polymethylsilsesquioxane particles detached from the toner particle surface may cause damage to the photoconductor and poor image quality.
[0053] The average particle size (median size) and particle size distribution of the particles in this embodiment are measured by the following procedure. First, 0.1 g of dried polyalkylsilsesquioxane particles were placed in a glass container with an inner diameter of 4 cm and a height of 11 cm, and 50 g of 2-propanol was added thereto to obtain a solution. Next, 4.5 cm from the tip of the ultrasonic disperser probe (inner diameter of tip: 7 mm) was immersed in the above solution, and dispersed by ultrasonic dispersion at an output of 20 W for 15 minutes to obtain a dispersion. Next, the median size and particle size distribution were measured using this dispersion using a CPS Instruments centrifugal sedimentation particle size distribution measuring device DC24000. The disk rotation speed was set to 24,000 rpm, and the true density of the polyalkylsilsesquioxane was 1.3 g / cm. 3 The instrument was calibrated using polyvinyl chloride particles with an average particle size of 0.476 μm before the measurement. The particle size distribution of the measured particles was plotted as a cumulative distribution from the smallest particle size side for the mass of each particle, and the particle size diameter D90 at 90% of the cumulative size was divided by the particle diameter D10 at 10% of the cumulative size (D90 / D10) and defined as the particle size distribution index.
[0054] (External additives) It is preferable to add an external additive to the surface of the resin composition used in electrophotography in order to improve the performance of the toner, such as fluidity, chargeability, and cleanability. In the toner of the present embodiment, silica particles having a particle size of about 100 nm to 300 nm, small silica particles having a particle size of about 10 nm to 60 nm, and titanium oxide can be added.
[0055] In addition to the above, at least one selected from the group consisting of amorphous silica, aluminum oxide, strontium titanate, organic fine particles, and silicone oil may be added as an external additive to impart fluidity. The external addition process for adding these external additives can be performed on any of spherical toner, pulverized toner, and magnetic toner. The silica or titanium oxide used as the external additive may have a particle size ranging from 0.001 μm to 1.0 μm. The silica or titanium oxide may have its surface hydrophobized in advance with a silane coupling agent, silicone oil, or the like. Although it depends on the type of printer used, the amount of silica particles having a particle size of about 100 nm to 300 nm is preferably 0.1 parts by weight or more and 1.0 parts by weight or less, and the amount of silica particles having a particle size of about 10 nm to 60 nm is preferably 0.5 parts by weight or more and 2.0 parts by weight or less, relative to 100 parts by weight of toner particles. This makes it possible to provide favorable fluidity and chargeability.
[0056] The silica or titanium oxide used in the toner of this embodiment is preferably contained in an amount of 0.1 parts by weight to 4.0 parts by weight based on 100 parts by weight of the toner particles. By adding silica as an external additive, it is possible to improve the chargeability, improve the image uniformity, etc., and also improve the flowability. If a large amount of silica is added, the charge increases and fogging and scattering are eliminated, but the image may have a low density. In addition, the addition of titanium oxide as an external additive prevents excessive charging and improves uniformity, but if a large amount of titanium oxide is added, the charge becomes low and the image may become high density. In addition, the external additives silica and titanium oxide may be able to alleviate these problems by adjusting their particle size and surface treatment. For example, by using silica with a large particle size, it can be used as an agent to prevent other external additives from sinking into the ground.
[0057] (Coloring agent) The colorant used in the toner of the present embodiment is not particularly limited and can be appropriately selected from known color pigments depending on the purpose. In the present embodiment, the colorant can be at least one selected from black toner, cyan toner, magenta toner, and yellow toner, and each color toner can be obtained by appropriately selecting the type of color pigment.
[0058] As the black colorant, for example, carbon black such as furnace black, acetylene black, channel black, etc. can be used, and in the case of magnetic toner, magnetite, etc. can be used. The yellow colorant may be a condensed nitrogen compound, an isoindolinone compound, an anthraquinone compound, an azo metal complex, or an aryl imide compound.Specific examples of the yellow colorant include Pigment Yellow 180, Pigment Yellow 185, Pigment Yellow 74, and Pigment Yellow 155. The magenta colorant may be a condensed nitrogen compound, anthraquinone, quinacridone compound, basic dye lake compound, naphthol compound, benzimidazole compound, thioindigo compound, or perylene compound. For example, Pigment Red 122, Pigment Red 184, Pigment Red 238, Pigment Red 254, Pigment Red 269, Pigment Red 257, etc. may be used. The cyan pigment may be a copper phthalocyanine compound and its compounds, or an anthraquinone compound, etc. For example, Pigment Blue 15, Pigment Blue 15:2, Pigment Blue 15:3, Pigment Blue 15:4, etc. may be used.
[0059] The content of the colorant is preferably from 1 to 10 parts by weight, more preferably from 3 to 7 parts by weight, based on 100 parts by weight of the binder resin.
[0060] [Toner manufacturing method] The toner may be produced by a conventional method, which involves weighing out and blending predetermined amounts of binder resin, release agent, colorant, charge control agent, etc., mixing them using a mixer or the like, kneading them using a kneading machine such as a twin-screw extruder, a heat roll (heat roll), or an extruder, cooling and solidifying them, pulverizing them with a pulverizer such as a jet mill, and then classifying them. The toner can be obtained by adding external additives to the classified toner particles. In the toner production method of the present embodiment, the internal additives are preferably a binder resin, a release agent, a colorant, and a charge control agent (CCA), which increases the charging speed and allows the saturated charge amount, i.e., a sufficient charge amount, to be obtained immediately, preventing contamination inside the machine and increasing the printing speed. The toner of the present embodiment is negatively charged, and this can be confirmed, for example, by agitating a developer in which the toner and carrier are mixed in a mixer or the like, and then measuring the charge amount by a blow-off method.
[0061] The toner of the present embodiment can be produced as follows. (Kneading process) First, a binder resin, a release agent which is a low softening point substance, polymethylsilsesquioxane particles, and a pigment or dye as a colorant are thoroughly mixed using a mixer such as a Henschel mixer or a ball mill, and the resulting mixture is melt-kneaded using a thermal kneader such as a heated roll kneader or an extruder to make the resin components compatible with each other, and in the resulting mixture, a low softening point substance, a pigment, a dye, and a magnetic material are dispersed or dissolved as necessary, and the resulting kneaded product is cooled and solidified, and then pulverized and classified to obtain a pulverized toner.
[0062] (External addition process) In order to improve the performance of the toner, such as fluidity, chargeability, and cleaning ability, an external additive such as silica or titanium oxide can be added. The amount of the external additive added in the external addition step of this embodiment is preferably 0.1 parts by weight to 4.0 parts by weight, more preferably 0.5 parts by weight to 4.0 parts by weight, and more preferably 1.0 parts by weight to 3.0 parts by weight, based on 100 parts by weight of the mother toner obtained in the pulverization step. This makes it possible to preferably prevent the occurrence of filming while preventing the particles from coalescing. Note that multiple types of external additives can be combined. The external addition step was performed on the toner of the present embodiment in order to carry out the fixability test described later, and is not an essential step in the production of the toner.
[0063] In addition to the above steps, a pretreatment step and / or a heat treatment step may be performed between the kneading step and the external addition step. When a pretreatment step (spheroidization treatment) is performed, additives such as silica or titanium oxide may be added. This can prevent coalescence due to exposure of the release agent. When a heat treatment process is performed, the pulverized toner that has been through the pulverization process can be subjected to a gas phase treatment using hot air at a temperature higher than the glass transition point of the binder resin and the melting point of the release agent. This makes it possible to control the shape of the base toner particles obtained by the kneading-pulverization method to a more uniform spherical shape, to increase the smoothness of the toner surface, and to reduce adhesion stress.
[0064] In addition, since the toner of this embodiment is printed by a two-component development method, a trickle development system is adopted in which the toner and carrier are mixed and put into a toner cartridge, and the toner and carrier enter the developing machine. This allows the carrier to be constantly refreshed, preventing carrier spent, etc. The ratio of toner and carrier in the toner cartridge is adjusted to toner:carrier = 80-90:20-10 (%). In both trickle development and normal two-component development, the mixture ratio of toner and carrier inside the developing device is preferably controlled by a magnetic permeability sensor or the like to toner:carrier=10-20:80-90(%).
[0065] In this embodiment, a two-component developing method is described, but the toner obtained as described above can also be used as a one-component developer. A one-component developer is one in which a magnetic substance added to a toner functions as a pigment without using a carrier. There are two types of one-component developers: a magnetic one-component developer with a magnetic substance added, and a non-magnetic one-component developer that is triboelectrically charged by a doctor blade. In this case, there is no need to control the carrier and toner concentration, so it is suitable for small devices. The toner containing the polymethylsilsesquioxane of the present invention can obtain a sufficient amount of charge even when used as a one-component developer.
[0066] When the toner of this embodiment is used as a normal one-component toner, a method can be used in which the toner is forcibly triboelectrically charged by a developing sleeve using a blade or roller, and the toner is transported by adhering to the sleeve.
[0067] [Other embodiments] In the toner for developing electrostatic images according to the embodiment described above, only polymethylsilsesquioxane particles are added as a charge control agent, but in other embodiments, only polymethylsilsesquioxane particles and a salicylic acid derived metal salt are added as a charge control agent (see Example 2). According to the present invention, it has been confirmed that sufficient chargeability cannot be obtained by simply adding a charge control agent, which is usually added externally to a toner, but that the charge acceptance of the toner is improved by adding polymethylsilsesquioxane particles internally. Furthermore, when polymethylsilsesquioxane is mixed with another charge control agent and added internally, a typical charge control agent tends to inhibit the charge acceptance of polymethylsilsesquioxane, resulting in a decrease in the charge acceptance of the toner. However, when a salicylic acid derived metal salt is used, it has been found that the effect on the charge acceptance is relatively small.
[0068] Therefore, it has good compatibility with the polymethylsilsesquioxane particles added thereto, and can be used as an agent for adjusting the chargeability of the toner. Examples of such salicylic acid derived metal salts include zinc salicylate, aluminum salicylate, iron salicylate, zirconium salicylate, calcium salicylate, and chromium salicylate. Of these, it is preferable to use zinc salicylate or aluminum salicylate, and it is more preferable to use aluminum salicylate (aluminum salt derived from salicylic acid). In this case, the content of the metal salicylate relative to 10 parts by weight of polymethylsilsesquioxane is preferably 5 parts by weight or more and 20 parts by weight or less, more preferably 7 parts by weight or more and 15 parts by weight or less, and even more preferably 8 parts by weight or more and 12 parts by weight or less.
[0069] Example 1 [Kneading process] 100 parts by weight of polyester resin as a binder resin, 4.0 parts by weight of pigment as a colorant, 1.0 part by weight of polymethylsilsesquioxane particles (Sunseal MP-01, manufactured by Tokuyama Corporation) as a charge control agent, and 5.0 parts by weight of paraffin wax (PARACOHOL6600P, manufactured by Nippon Seiro Co., Ltd.) were mixed and kneaded in a twin-screw extruder (PCM43, manufactured by Ikegai Co., Ltd.). The polymethylsilsesquioxane particles used in Example 1 were hydrophobized polymethylsilsesquioxane particles with an average particle size (median size) of 0.15 μm, a particle size distribution index of 2.1, and a hydrophobicity of 57% by volume. The paraffin wax (PARACOHOL6600P manufactured by Nippon Seiro Co., Ltd.) had a melting point of 89° C. and an acid value of 3 mgKOH / g. [Crushing process] Thereafter, the obtained kneaded product was pulverized and adjusted to an average particle size of 7.5 μm using a jet pulverizer (I-5 manufactured by Nippon Pneumatic Co., Ltd.) to obtain a base toner.
[0070] Example 2 A toner was obtained by carrying out the same steps as in Example 1, except that in the kneading step, 1.0 part by weight of aluminum salicylate was further mixed with 1.0 part by weight of the polymethylsilsesquioxane particles.
[0071] Example 3 A toner was obtained by carrying out the same steps as in Example 1, except that in the kneading step, the mixed amount of polymethylsilsesquioxane particles was 5.0 parts by weight.
[0072] Example 4 A toner was obtained by carrying out the same steps as in Example 1, except that in the kneading step, the mixed amount of polymethylsilsesquioxane particles was 10 parts by weight.
[0073] Comparative Example 1 A toner was obtained in the same manner as in Example 1, except that in the kneading step of Example 1, 1.0 part by weight of aluminum salicylate was mixed in place of the polymethylsilsesquioxane particles.
[0074] Comparative Example 2 A toner was obtained in the same manner as in Example 1, except that in the kneading step of Example 1, 1.0 part by weight of a resin-based charge control agent (manufactured by Fujikura Chemical Industries, Ltd., FCA-2521NJ) mainly composed of styrene resin was mixed in place of the polymethylsilsesquioxane particles.
[0075] Comparative Example 3 A toner was obtained in the same manner as in Example 1, except that in the kneading step of Example 1, polymethylsilsesquioxane particles were not mixed (charge control agent was not added internally).
[0076] Comparative Example 4 A toner was obtained in the same manner as in Example 1, except that in the kneading step of Example 1, 1.0 part by weight of dimethylpolysiloxane was mixed in place of the polymethylsilsesquioxane particles.
[0077] Comparative Example 5 A toner was obtained in the same manner as in Example 1, except that in the kneading step of Example 1, 1.0 part by weight of aluminum salicylate and 1.0 part by weight of dimethylpolysiloxane were mixed in place of the polymethylsilsesquioxane particles.
[0078] Comparative Example 6 In the kneading step of Example 1, 1.0 part by weight of aluminum salicylate and dry silica (surface area 200 m) were used in place of the polymethylsilsesquioxane particles. 2 A toner was obtained in the same manner as in Example 1, except that 1.0 weight percent of the toner particles (1.0 weight percent / g) was mixed and an ester wax (WE-5 manufactured by NOF Corp.) was used instead of the paraffin wax.
[0079] Comparative Example 7 In the kneading step of Example 1, 1.0 part by weight of aluminum salicylate and acrylic organic particles (D 50 A toner was obtained in the same manner as in Example 1, except that 1.0 part by weight of 1.0 part by weight of sieve diameter 0.4 μm was mixed and an ester wax (WE-5 manufactured by NOF Corp.) was used instead of the paraffin wax.
[0080] <Measurement of toner charge amount> 0.1 g of the toner obtained in each example and 0.9 g of ferrite carrier (Y-35-K manufactured by Kanto Denka Kogyo Co., Ltd.) were placed in a 100 cc PP container and stirred in a ball mill (ANZ-60s manufactured by Nitto Kagaku Co., Ltd., roll width 90 mm, 120 rpm). Samples were taken 0.5 minutes, 1.0 minutes, 3.0 minutes, 5.0 minutes, 10 minutes, 30 minutes, and 60 minutes after the start of friction. Next, the amount of charge of the frictionally charged developer (toner-carrier mixture) was measured using a suction-type charge measurement device (Trek 212HS) with two-component specifications (approximately 0.2 g was placed in a special container and sucked up through mesh #635). The saturated charge amount was the value at which the toner charge amount was maximum 60 minutes after the start of friction. The physical properties of the ferrite carrier used in this charge amount measurement are as follows: Saturation magnetization σ s :62Am 2 / kg residual magnetization σ r :0.3Am 2 / kg Coercive force H c : 0.5kA / m Core material: Cu-Zn Particle size D 50 :35μm Surface treatment: acrylic resin
[0081] 1 to 3 are graphs in which the vertical axis represents the charge amount (absolute value) and the horizontal axis represents the friction time up to 60 minutes in Examples 1 to 4 and Comparative Examples 1 to 7. Table 1 shows the slope of the charge amount at the start of friction to the charge amount 3 minutes after the start of friction, expressed as the charging rate [μC / (g·min)]. In this case, the toner's saturated charge is preferably 28 μC / g or more, more preferably 31 μC / g or more, even more preferably 33 μC / g or more, and most preferably 35 μC / g or more. This allows the toner to be sufficiently charged, enabling high-quality printing. The toner's charging speed is preferably 5.0 μC / g·min or more, more preferably 5.8 μC / g·min or more, even more preferably 6.0 μC / g·min or more, and most preferably 6.5 μC / g·min or more. This allows high-speed printing while minimizing uneven charging.
[0082] According to Table 1, Example 1, in which 1 part by weight of polymethylsilsesquioxane particles was added, had a large saturated charge amount and a fast charging speed, and the saturated charge amount was maintained at a stable high value from 30 to 60 minutes after the start of friction. Example 3, in which 5 parts by weight of polymethylsilsesquioxane particles were added, and Example 4, in which 10 parts by weight of polymethylsilsesquioxane particles were added, also had a high saturated charge amount and a fast charging speed, but in Example 4, the charge amount gradually decreased from 10 minutes after the start of friction, when the saturated charge amount was obtained, to 60 minutes. This is thought to be because the amount of polymethylsilsesquioxane particles added exceeded a predetermined value, and the amount of polymethylsilsesquioxane particles present on the toner surface also increased, resulting in a slight inclination of the balance between power supply to the toner and leakage to the leakage side. Therefore, charge leakage may be somewhat more likely to occur, making it difficult to continue to supply a large amount of charge to the toner. Therefore, from the viewpoint of saturated charge amount and charging speed, it is more preferable to set the amount of polymethylsilsesquioxane particles added internally to less than 10 parts by weight. [Table 1]
[0083] <Environmental stability measurement of toner charge amount> Standard environmental conditions (NN) were 20-25°C and 40-60RT%, low temperature and low humidity conditions (LL) were 10-15°C and 20-30RT%, and high temperature and high humidity conditions (HH) were 30°C and 80RT%, and after frictional charging for 60 minutes under each constant temperature and humidity condition, the charge amount was measured in the same manner as described above. The measurement results for the environmental stability of the charge amount are shown in Table 2. The environmental fluctuation rate (absolute value) was also calculated using the following formula. The lower the fluctuation rate, the more stable the chargeability of the toner. Fluctuation rate of LL relative to NN (%) = [charge amount NN - charge amount LL] / charge amount NN x 100 Fluctuation rate of HH relative to NN (%) = [charge amount NN - charge amount HH] / charge amount NN x 100
[0084] [Table 2]
[0085] As shown in Table 2, Example 1 in which polymethylsilsesquioxane particles were added had a large amount of charge and a low rate of change under both low temperature and low humidity conditions and high temperature and high humidity conditions. From the viewpoint of environmental stability, the fluctuation rate of LL is preferably 10% or less, more preferably 5% or less, and the fluctuation rate of HH is preferably 7% or less, more preferably 4% or less, and even more preferably 3% or less. In particular, in an HH environment, moisture in the air can cause charge leakage. It was confirmed that the toner of the embodiment, which contains polymethylsilsesquioxane particles, can suppress charge leakage from the toner, improve environmental stability, and is less susceptible to deterioration in toner performance over long-term use, resulting in a toner with excellent storage stability.
[0086] <Storage modulus of toner> The storage modulus G' of the toner was measured under the following conditions using a dynamic viscoelasticity measuring device (Rheosol-G3000 manufactured by UBM Corporation). Measurement method: Dynamic viscoelasticity measurement (sine wave) Measurement mode Temperature dependence ·Chuck Parallel plate Parallel diameter 20mm Gap: 1mm Type of excitation: Continuous excitation - Initial load manual control Conditions: Start: 40℃, Step: 2℃, End: 200℃, Slope: 5℃ 1Hz1deg (heat from room temperature at a temperature rise rate of 2℃ / min, apply stress of 1.0Hz1deg in the temperature range from 40℃ to 200℃, and detect the response) Torque Fs 2.04Kg*cm The dynamic viscosity η' and shear rate ω shown in Figures 6 and 7 were measured at a fixed temperature of 130°C to measure frequency dependence. From the above measurements, data such as storage shear modulus (G'), loss shear modulus (G''), vibration absorption coefficient (loss tangent) (tan δ), and dynamic viscosity (η') were obtained.
[0087] 4 and 5 show the temperature characteristics of dynamic viscoelasticity, and the logarithm of the storage modulus G' measured under the above conditions was taken to confirm the temperature dependence of the storage modulus G'. Fig. 4 is a graph showing the results of a comparison of the storage modulus G' of Comparative Example 3 (none), Example 1 (1 part by weight), Example 3 (5 parts by weight), and Example 4 (10 parts by weight) when the amount of polymethylsilsesquioxane particles added was changed. Fig. 5 is a graph showing the results of a comparison of the storage modulus G' of Example 1 (polymethylsilsesquioxane), Comparative Example 1 (aluminum salicylate), and Comparative Example 4 (dimethylpolysiloxane) when the type of charge control agent added was changed.
[0088] As shown in Example 1 of Figure 4, by adding polymethylsilsesquioxane particles, the storage modulus G' becomes a preferable value in the general fixing range of 130°C to 150°C. This provides excellent offset resistance, and the toner is preferably softened in the fixing region of the toner, penetrates into the paper fibers, and is cooled and fixed as it is after the fixing roller separates from the paper. In Example 4, the storage modulus G' tends to be slightly higher on the high temperature side. Depending on the printing machine, if the storage modulus G' is high when the toner is in the fixing area, the toner may not be softened sufficiently.
[0089] In Comparative Example 1 (aluminum salicylate) in Figure 5, the storage shear modulus G' is lower than in the Examples. Depending on the printing machine, it may not reach the storage shear modulus G' required for fixing to paper. This may cause the toner to not be fixed to the paper well, resulting in offset. In addition, in Comparative Example 1, no peak was observed near the glass transition point (70°C), and it can be seen that the storage modulus G' did not change sharply. From this, it is considered that the toner in Comparative Example 1 has a lower thixotropy than in the Examples, and the toner melts even at low temperatures and continues to remain in a soft state, which may cause problems with fixability. On the other hand, in Example 1, since the storage modulus G' changes sharply near the glass transition point, the toner has high thixotropy, and the viscosity η of the toner is easily reduced by the stress of the fixing roller, improving the fixation to paper and enabling high-quality printing.
[0090] Figures 6 and 7 show the frequency dependence of the dynamic viscosity coefficient η', which is the logarithm of the dynamic viscosity coefficient η' measured under the above conditions at 130°C (near the fixing temperature) and the shear rate ω (rad / sec). Fig. 6 is a graph showing the results of comparing the frequency dependence of dynamic viscosity η' for Comparative Example 3 (no addition), Example 1 (1 part by weight), Example 3 (5 parts by weight), and Example 4 (10 parts by weight) when the amount of polymethylsilsesquioxane particles added was changed. Fig. 7 is a graph showing the results of comparing the frequency dependence of dynamic viscosity η' for Example 1 (polymethylsilsesquioxane), Comparative Example 1 (aluminum salicylate), and Comparative Example 4 (dimethylpolysiloxane) when the type of charge control agent added was changed.
[0091] In the graphs of Figures 6 and 7, the greater the downward slope on the low speed side (near 0.5 rad / sec), the higher the thixotropy of the toner can be evaluated. Therefore, according to Figure 6, Examples 1, 3, and 4 have higher thixotropy than Comparative Example 3. Of these, Examples 3 and 4 in particular have high thixotropy, and it was found that the greater the amount of polymethylsilsesquioxane particles added, the more preferable it is. Such high thixotropy improves fixability when pressure stress is applied during fixing, and it is also thought that thixotropic hysteresis makes it difficult for characters to become blurred after printing. In Fig. 7, Example 1 has a larger slope and higher thixotropy than Comparative Examples 1 and 4. This shows that, when comparing the types of charge control agents added, the fixation is better when polymethylsilsesquioxane is added than when aluminum salicylate and dimethylpolysiloxane are added. This is thought to be due to the network structure of polymethylsilsesquioxane.
[0092] <Observation of toner cross section> 8 and 9 are SEM images obtained by observing the cross sections of the toner particles of Examples 1 and 4 of the present invention. As shown in Fig. 8 and Fig. 9, it was confirmed that polymethylsilsesquioxane particles 20 were dispersed inside the toner particles 10. As shown in Fig. 8, in Example 1, in which 1 part by weight of polymethylsilsesquioxane particles is added, it is found that polymethylsilsesquioxane particles 20 are suitably dispersed inside toner 10. In Example 4 shown in Fig. 9, since 10 parts by weight of polymethylsilsesquioxane particles 20 are added, they slightly aggregate inside toner 10, and some of them begin to exist on the toner surface. In other words, it is suggested that even if the amount of polymethylsilsesquioxane particles 20 added is excessive, the saturated charge amount does not become larger than that.
[0093] The observation method using a scanning electron microscope is as follows. 1: The sample is embedded in epoxy resin 30 (Konishi Bond Quick 30 is used) and then hardened. 2: The hardened sample is cut using a microtome (Leica Microsystems, RM2255) to prepare a cross section. 3: The cross section of the fabricated sample is observed using a field emission scanning electron microscope (JEOL Ltd., JSM-7000).
[0094] Although a preferred embodiment of the present invention is as described above, the present invention is not limited thereto. It is understood that various other embodiments can be made without departing from the spirit and scope of the present invention. Furthermore, although the actions and effects of the configuration of the present invention are described in this embodiment, these actions and effects are merely examples and do not limit the present invention.
Claims
1. A toner for developing an electrostatic image, comprising a binder resin, a colorant, a release agent, and a charge control agent, the charge control agent is made of polymethylsilsesquioxane particles and is added to the toner for developing electrostatic images, The average particle size of the polymethylsilsesquioxane particles is 0.05 μm or more and 0.3 μm or less, A toner for developing electrostatic images, the absolute value of which is 30 μC / g or more.
2. 2. The toner for developing electrostatic images according to claim 1, wherein said charge control agent comprises said polymethylsilsesquioxane particles and an aluminum salt of a salicylic acid derivative.
3. 2. The toner for developing electrostatic images according to claim 1, wherein the absolute value of the charging speed is 6.0 μC / g·min or more.
4. The toner for developing electrostatic images according to claim 1 , wherein the binder resin comprises a polyester resin.
5. 3. The toner for developing electrostatic images according to claim 1, wherein the polymethylsilsesquioxane particles are contained in an amount of 1 part by weight or more and 8 parts by weight or less per 100 parts by weight of the binder resin.
6. 3. The toner for developing electrostatic images according to claim 1, wherein a ratio of average particle diameters of the toner for developing electrostatic images and the polymethylsilsesquioxane particles (toner particles / polymethylsilsesquioxane particles) is 25 or more and 150 or less.
7. a kneading step of kneading a binder resin, a colorant, a charge control agent, and a release agent to obtain a kneaded product; a pulverization step of pulverizing the kneaded product to obtain a mother toner having an average particle size of 5 μm or more and 10 μm or less; an external addition step of adding amorphous silica and / or titanium oxide to the mother toner; Including, In the method for producing a toner for developing electrostatic images, the charge control agent added to the kneaded product is made of polymethylsilsesquioxane particles having an average particle size of 0.05 μm or more and 0.3 μm or less.
8. 7. The method for producing a toner for developing electrostatic images according to claim 6, wherein the charge control agent added to the kneaded product comprises polymethylsilsesquioxane particles having an average particle size of 0.05 μm or more and 0.3 μm or less and a metal salicylate.
Citation Information
Patent Citations
Electrostatic charge image developer
JP1988101854A
Electrostatic charge image developer
JP1988101855A
Electrostatic charge image developer
JP1993323652A
Organic-inorganic composite particles, their production and use
JP1997197705A
Polymethylsilsesquioxane particle and toner external additive
JP2020029547A